Early result: randomized controlled trial of treatment for intermittent claudication - Khan, Mazari Fayyaz Ali; Sumit, Gulati; Lee, H. L. D.; Tapan, Mehta; Abdul Rahman, Mohd Norhisham Azmi; Ian, Chetter (Wiley, 2008)
Objective: To compare angioplasty (PTA), supervised exercise (SEP) and PTA + SEP in the treatment of intermittent claudication (IC) due to femoro-popliteal disease Methods: Over a 6 years period, 178 patients (108 men, median age 70 years) with angioplastiable femoro-popliteal lesions were randomized to: PTA, SEP or PTA + SEP. Patients were assessed prior to and at 1 & 3 month post treatment. ISCVS outcome criteria (Ankle pressures, treadmill walking distances) and Quality of Life (QoL) questionnaires (SF36 and VascuQoL) were analysed. Results: All groups were well matched at baseline. 21 patients withdrew. Intra group analysis: All groups demonstrated significant clinical and QoL improvements (Friedman test, p < 0·05). SEP (59 patients, 8 withdrew) – 62·7% of patients (n = 32) improved following treatment [20 mild, 9 moderate, 3 marked], 27·4% (n = 14) no improvement and 9·8% (n = 5) deteriorated. PTA (60 patients, 3 withdrew) – 66·6% of patients (n = 38) improved following treatment [19mild, 10 moderate, 9 marked], 22·8% (n = 13) no improvement and 10·5% (n = 6) deteriorated. PTA + SEP (59 patients, 10 withdrew) – 81·6% of patients (n = 40) improved following treatment. [10 mild, 17 moderate, 13 marked], 14·2%% (n = 7) no improvement and 4·0% (n = 2) deteriorated Inter group Analysis: PTA + SEP produce a much greater improvement in clinical outcome measures than PTA or SEP alone, but there was no significant Q0L advantage (Kruskal Wallis test, p > 0·05). Conclusion: SEP should be the primary treatment for the patients with claudication and PTA should be supplemented by a SEP.